A risky shift? An exploration of the measurement equivalence of entrepreneurial attitudes and entrepreneurial orientation across socioeconomic gradients - Gloss, A.; Pollack, J.; Ward, Mary (2017)
While entrepreneurial orientation (EO) is often conceptualized on a firm level of analysis, scholarship has highlighted that firm-level strategy is influenced by the psychology of managers. Because an individual's psychological approach to risk-taking is influenced by socioeconomic factors, we explored whether responses to risk-taking items in scales of individual-level entrepreneurial attitudes and firm-level EO are influenced by socioeconomic status and the socioeconomic development of regions. Testing for measurement equivalence (ME), we found evidence consistent with the inference that items relating not only to risk-taking, but also to innovativeness and proactivity, are thought of differently according to socioeconomic influences on individual and regional levels of analysis. We discuss the implications of our results including the need for researchers to test for ME when exploring entrepreneurial attitudes and EO across socioeconomic gradients.